The use of agile methodologies and their contribution to innovation of the business model: a study of multiple cases in the context of incubators and startups - Guimarães Mota, Patrícia; Luiz Barbosa da Silva, André; Limongi França Coelho, Ricardo (REGEPE Entrepreneurship and Small Business Journal, 2022)
Purpose: to understand the phenomenon of agile methodologies and their application in the innovation of existing business models. Methodology: a qualitative study, with a multiple case approach. Main results: the empirical findings confirmed the importance of incubator contributions to the development of innovation in incubated startups. Theoretical or methodological contributions: the research corroborates what the literature says on the subject and contributes useful information to the process of implementing agile methodologies. Relevance and originality: this study is relevant because it deals with challenges that are still little known in the implementation of agile methodologies, thus collaborating to fill the gap in the literature. Social or managerial contributions: the results of this study can help startup managers to deal with the adversities in implementing and adapting to agile methodologies; and to seek a more effective monitoring of the incubator throughout this process.